Glucose-mediated template-free synthesis of hollow CuO microspheres. Issue 26 (17th April 2018) - Zhou, Hai; Kang, Min; Qin, Biao; Zhao, Ning; Wu, Dong; Lv, Baoliang; Wang, Qingjie
Abstract : In this work, we demonstrated a facile template-free method for the preparation of hollow CuO microspheres via a conventional hydrothermal reaction. Abstract : In this work, we demonstrated a facile template-free method for the preparation of hollow CuO microspheres via a conventional hydrothermal reaction. The hollow architecture formed directly during the hydrothermal treatment of copper nitrate and glucose, without the use of template, precipitant and calcination process. The effects of reaction time, reaction temperature and glucose concentration were investigated in detail. On the basis of experimental results, the formation of hollow CuO microspheres probably proceeded via self-assemble process and the subsequent Ostwald's ripening. This synthetic strategy strongly depended on the characteristics of copper nitrate, which made it could not extend to other copper salts and/or nitrates. Even though, glucose still showed efficient morphology controlling ability with respect to nanosized transitional metal oxides, which could be used for the controllable synthesis of nanomaterials.